Nonlocal Integrated Solutions for a Class of Abstract Evolution Equations - Lizama-Yanez, C; Rueda-Sanchez, S (Springer Netherlands, 2019)
In this article we show the existence of at least one integrated solution of a semilinear second order differential equation with an extra convolution term and nonlocal initial conditions. As main tool we use properties of the Hausdorff measure of noncompactness and fixed point theorems. © 2018, Springer Nature B.V.